Assessment of global coagulation function under treatment with emicizumab concomitantly with bypassing agents in haemophilia A with inhibitor (UNEBI Study): multicentre open-label non-randomised clinical trial. Issue 2 (17th February 2022) - Ogiwara, Kenichi; Taki, Masashi; Suzuki, Takashi; Takedani, Hideyuki; Matsushita, Tadashi; Amano, Kagehiro; Matsumoto, Masanori; Nishio, Kenji; Shima, Midori; Kasahara, Masato; Nogami, Keiji
Abstract : Introduction: Subcutaneous emicizumab prophylaxis substantially reduces bleeding episodes in patients with haemophilia A (PwHA) and factor VIII inhibitor. However, thrombotic events occurred in some PwHA with inhibitor who had received high cumulative doses of activated prothrombin complex concentrates at their breakthrough bleeds, when they were also given prophylactic emicizumab. After that, although the recommended guidance was proposed for bypassing agents (BPAs) therapy under emicizumab prophylaxis for haemostatic management, detailed investigation(s) is(are) required to elucidate the safe and appropriate dose of BPAs to use concomitantly with emicizumab prophylaxis. Methods and analysis: In the UNEBI Study, 60 PwHA with inhibitor will be enrolled for a maximum duration of 3 years, and samples of 20 events following concomitant use of BPAs with emicizumab will be collected. An 'event' is defined as obtaining blood samples before and after administration of BPA when a breakthrough bleed or a surgical procedure occurs. The coagulation potential in the obtained samples will be measured by global coagulation assays. The primary endpoint is the degree of improvement in the maximum coagulation rate by clot waveform analysis (CWA) before and after administration of fixed-dose BPAs. This parameter obtained from CWA, which is triggered with an optimally diluted mixture of prothrombin time/activated partial thromboplastin time-reagents, is reported to be an excellent marker for assessing the degree of improvement in coagulation potential in emicizumab-treated plasma. Ethics and dissemination: The UNEBI Study was approved by the Japan Certified Review Board of Nara Medical University. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number: jRCTs051190119.